An Error Analysis Of The Choir Performance at SDN 2 Sukamanah, Tasikmalaya In Singing 'Mengheningkan Cipta' From A Musical Perspective - Cindy Aurellia; Resa Respati; Aini Loita (Genderang Asa: Journal of Primary Education, 2025)
This study aims to analyze musical errors in the choir performance of SDN 2 Sukamanah, Tasikmalaya, when singing the national mandatory song Mengheningkan Cipta. This topic is important because mandatory songs carry educational and symbolic values that should be understood from the elementary level. The method used is content analysis with a qualitative approach. Data were obtained through direct observation and video recordings, then analyzed both auditorily and notationally. The results revealed several musical deviations, such as pitch inaccuracies, inappropriate use of vocal ornamentation, application of staccato techniques not present in the original score, and alterations in note values that disrupted the rhythmic structure. These deviations reflect a habit of free interpretation that has developed in the school environment but is not in harmony with the solemn character of the song. This study emphasizes the importance of proper musical education so that students can understand and express national mandatory songs both musically and contextually in accordance with the values they convey.